Black Point and Black Discolouration Diseases of Wheat in India During 1995-96 to 2002-2003 - A.K. SHARMA; M.S. SAHARAN; J. KUMAR; K.S. BABU; A.K. SINGH; MANOJ KUMAR; S.P. SINGH; KAMLESH KUMAR; SUNIL KUMAR; S.K. MANN; S.K. MANN; S.S. KARWASARA; et al. (Seed Research, 2026)
Black point and black discolouration diseases of wheat are gradually becoming important as they affect the trade. Both these grain maladies are many times, confused with Karnal bunt disease (Tilletia indica Mitra) which has great quarantine implications. Wheat grain samples were analyzed for black point for eight years (1995-96 to 2002-03) and for black discolouration for six years (1996-97 to 1997-98 & 1999-2000 to 2002-03) from different wheat growing states of India. The study indicated that black point and discolouration were prevalent during 1995-96 to 2002-03 in most of the states (from where samples were analyzed) but there was difference in the incidence of both diseases. During 1995-96, in Punjab and Haryana, 93.9 and 77.5 per cent samples showed the black point level of infection of 0.1-1.7 and 0.1-3.0 per cent, respectively. During 1996-97, in Haryana, Punjab and U.P. majority of the samples were in the range of 0.05-2.4 per cent disease level. Incidence of black point in India during 1997-98 was very high (85.9% infected samples) whereas, during 1999-00, 74.2 per cent samples/were found infected. During 2000-01 and 2001-02, Punjab had maximum infection of 90.5 per cent and 91.4 per cent, respectively, whereas, in 2002-03, the highest number of infected samples were from central and eastern U.P. (83.0%). Black point incidence was the highest during 1997-98, followed by 2001-02 as compared to other years. Black discolouration incidence was observed from 0.05 to 1.0 per cent at most of the places in North West Plain Zone (NWPZ) during 1996-97. Black discolouration samples ranged 41.5 per cent to 77.4 per cent during 1997-98 and during 1999-00, the range was between 39.7 to 81.7 per cent in different states. Black discolouration incidence was the highest in Punjab in 1999-00 to 2002-03. In general, these grain infections were higher in the NWPZ as compared to the central and peninsular zones. However, in certain years, some exceptions were noted.